TINJAUAN TERHADAP PERJANJIAN KREDIT DENGAN JAMINAN FIDUSIA - Ratni Sadiah (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACT This thesis title is "Overview Of Credit Agreement With Fiduciary" This thesis is a study of Law number 42 of 1999 on fiduciary. The main problem of this study is that turns out to be a debtor does not mengertimengensi hukun fiduciary while being creditors only after the customer as much as possible, as a result of this, many misunderstandings regarding the implementation of the law fiduciary, both creditors and debtors. This study is intended to troubleshoot problems arising from the fiduciary can be overcome and the Act - legislation fiduciary as laws to protect the rights of creditors and the rights of creditors.       The purpose of these studies in order for the parties that entered into fiduciary truly understand the implementation of law number 42 of 1999 on fiduciary. The research method of this thesis is more emphasis on normative juridical, this thesis merekornendasikan conceptual and practical implementation of law number 42 of 1999 on fiduciary, that the Ministry of Justice and Human Rights, in this case the Registration Office Eidusia to do counseling by the law under which most of them become creditors in financial institutions, and the financial institutions in particular iembaga lembagr financing relating to the fiduciary agreement, it relates to an increase in human resources in the financial institutions, especially the security inventasi.